Evaluation of the Fate of Nitrate and Analysis of Shallow Soil Water using Geo-electrical Resistivity Survey - Nur Islami (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Evaluation of the fate of nitrate and analysis of shallow soil water in a tobacco plantation area were conducted using integration of soil properties and hydrogeochemical analysis, and geo-electrical resistivity methods, taking measurements four times within a three-month period. The sampling data were taken in two areas: a fertilized and a nonfertilized zone. Chemical fertilizer was introduced to the fertilized zone after the first data acquisition. Hydrogeohemical analysis of the soil water was conducted from the surface to a depth of 1 m at an interval of 25 cm. The results show that the cations in the soil water were quite comparable for each monitoring time. Conversely, relatively larger changes in anion content occurred at the surface until a depth of 1 m. In particular, the nitrate concentration reached its maximum level at about 67 days after fertilization and returned to its initial value approximately 195 days after fertilization. The geo-electrical resistivity profiles exhibited no indication of low resistivity values prior to fertilization near the surface. However, lower resistivity values were found in the fertilized zone at the second and third measurement. The result shows that the adjoining environment dissolved the nitrate concentration in the pore soil within the three-month time period.